The Psychological Comparison of the Red Queen and White Queen in Alice Through The Looking Glass: English - Suryadewi, Ni Kadek; Skolastika, I Made Perdana (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study analyze the psychological aspects of the secondary characters, namely the Red Queen and the White Queen in the film Alice through the Looking Glass (2016). This study focuses on how the differences of their Id, Ego, and Superego explains their behavior and how they strategize to resolve their conflicts. This study aims to explore the psychological aspects that shape character development and its relevance to narrative conflict resolution. This study uses a descriptive qualitative method, using observation and recording techniques to collect data. Data sources include films and their transcripts from script.com written by Linda Woolverton. Data collection was carried out by watching and analyzing films, capturing important scenes, and interpreting character actions based on theoretical frameworks. The theory by Sigmund Freud (1923) was applied to categorize examples of Id, Ego, and Superego in each character, while the theory of conflict management model by Thomas and Kilmann (1970) used to analyze how the two sisters resolve their problems. The findings reveal that the Red Queen is dominantly driven by the Id, with 8 data reflecting impulsive and vengeful behavior rooted in unresolved childhood trauma. In contrast, the White Queen is governed by the Superego, with the 4 data displaying moral values ??such as wisdom and empathy. Their conflict is resolved through collaborative strategies, emphasizing a shared recognition of past mistakes that led them to become enemies. This study contributes to the understanding of psychological character development in film by demonstrating the interplay of internal psychological dynamics and their role in shaping narrative structure. It highlights how Freud’s framework and conflict resolution theory provide important insights into character motivations and how the resolution of these conflicts can provide a broader perspective on the significance of psychology in storytelling and film analysis.